Analisis Syair Al-Mazallatu Kufrun Dalam Diwan Asy-Syafi’i (Kajian Semiotika Charles Sander Pierce) - Hakiki, Ahmad Sirojul (An Nazhair: Journal of Arabic Education, 2025)
Poetry, known as "sya'ir" in Arabic, is a concise and meaningful expression. It is characterized by the use of short sentences and consists of only a few lines. In poetry, there are many expressions conveyed indirectly, requiring deeper interpretation. The purpose of this research is to explore the signs in the poem "Al-Mazallatu Kufrun" by Imam Shafi'i using Charles Sander Pierce's semiotics theory. This study employs a descriptive qualitative method with an objective approach. The data analysis technique used is descriptive analysis. The results of this research reveal the existence of signs based on the relationship between signs and their signifiers, namely icons and indexes. Icons in the above poem are found in the first and third stanzas with the aim of expressing the sign of not depending on others in worldly matters because one feels content with the provision of Allah SWT, known as "qana'ah." This is because the provision from Allah SWT is what humans truly need, not necessarily what they desire. Furthermore, indexes in the poem are present in the second and fourth stanzas, intending to explain the consequences of fearing only Allah and accepting sincerely what God provides.